Online Education During COVID-19 Lockdown Period in MBA Colleges : An Analytical Study Conducted in Kochi - T. S., Aravind (Indian Journal of Computer Science, 2021)
The educational structure from elementary to tertiary stage crashed during the lockdown period of Novel Coronavirus epidemic (COVID-19) not just in India but around the globe. This research discusses online teaching-learning modes used by M.B.A. teachers and students in Kochi. The aim of the paper was to examine the necessary essentialities of online teaching-learning in education amid the COVID-19 pandemic and how current resources of educational institutions can effectively turn formal education into online education with the aid of virtual classes and other pivotal online tools in this constantly evolving educational environment. The paper uses an analytical methodology to study what teachers and students feel about online teaching-learning modes with simple percentage tool, and indeed how online teaching-learning modes are put into action. The purpose of this study is to draw a complete picture of ongoing teaching and learning activities during the Novel Corona epidemic so as to resolve disruptions and return to standard practice in educational institutions.